Coos, booms, and hoots: The evolution of closed‐mouth vocal behavior in birds. (1st August 2016) - Riede, Tobias; Eliason, Chad M.; Miller, Edward H.; Goller, Franz; Clarke, Julia A.
Abstract: Most birds vocalize with an open beak, but vocalization with a closed beak into an inflating cavity occurs in territorial or courtship displays in disparate species throughout birds. Closed‐mouth vocalizations generate resonance conditions that favor low‐frequency sounds. By contrast, open‐mouth vocalizations cover a wider frequency range. Here we describe closed‐mouth vocalizations of birds from functional and morphological perspectives and assess the distribution of closed‐mouth vocalizations in birds and related outgroups. Ancestral‐state optimizations of body size and vocal behavior indicate that closed‐mouth vocalizations are unlikely to be ancestral in birds and have evolved independently at least 16 times within Aves, predominantly in large‐bodied lineages. Closed‐mouth vocalizations are rare in the small‐bodied passerines. In light of these results and body size trends in nonavian dinosaurs, we suggest that the capacity for closed‐mouth vocalization was present in at least some extinct nonavian dinosaurs. As in birds, this behavior may have been limited to sexually selected vocal displays, and hence would have co‐occurred with open‐mouthed vocalizations.